the Educating On Preventing Verbal Bullying Through a Social Literacy Approach at SDN 2 Baubau - Kosilah Kosilah; Maria Ulfa; Yurfiah; Annisa; Asmina (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service activity is designed as a primary school-based intervention focusing on strengthening students' social-emotional capacity to prevent verbal bullying. This background is based on the phenomenon of verbal bullying in primary schools, which is often seen as normal interaction, but in reality has a significant impact on students' psychological and social development. In addition, there is a gap in students' social literacy, especially in the aspects of empathetic communication, social awareness, and emotion management. The activity took place at SDN 2 Baubau involving 45 students from three classes. The method used was a participatory-educative approach. The results included improved student understanding of verbal bullying, changes in attitude towards negative behaviour, and enhanced healthy social communication skills. Strategically, the activity is innovative in integrating social literacy as a preventive approach in the elementary school context, potentially contributing to the development of a school-based intervention model.